Evaluation of Smallholder Oil Palm Plantation Sustainability in Tidal Lowlands of Pulau Rimau Sub-District of Banyuasin Regency - Laily Muharani; Muhammad Yazid; Dessy Adriani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Muharani L, Yazid M, Adriani D. 2020. Evaluation of smallholder oil palm plantation sustainability in tidal lowlands of Pulau Rimau Sub-District of Banyuasin Regency. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 80-88.Oil palm is one of the estate commodities that has an important role in the economic activities of the people. Smallholder oil palm plantation as part of the estate still face several constraints, including lack of productivity, institutional inactivity, plantation management that do not meet the standard, farmers' lack of knowledge, and difficulty in obtaining credit. Due to these constraints, oil palm plantation sustainability is put into priority. Oil palm development issues are discussed not only on the economic aspects but also on the environmental aspects. This research is aimed at analyzing the level of oil palm sustainability and evaluating the condition of smallholder oil palm plantations according to the stages of plant development. This research used survey method and was carried out in tidal lowlands of Pulau Rimau Sub-district, Banyuasin Regency in August-September 2019. Smallholder oil palm households were selected using proportionate stratified random sampling. The results showed that there were three aspects of sustainability that were in low criteria, namely institutional, social, and technical aspects. Whereas, economic and environmental aspects were in medium criteria. The average sustainability value of non productive and productive oil palm plantations was in low criteria. Smallholder oil palm households were expected to understand and follow the standards set by ISPO, with the support from local governments and related agencies.